2013
DOI: 10.4103/0972-0707.114357
|View full text |Cite
|
Sign up to set email alerts
|

A survey of attitude and opinions of endodontic residents towards regenerative endodontics

Abstract: Aim:The objective of this survey was to study the level of awareness, current state of knowledge and opinions towards regenerative endodontic treatments amongst the endodontic residents of India.Settings and Design:Questionnaire based survey was designed.Materials and Methods:After approval from the organizing committee of 26th Federation of Operative Dentistry of India and 19th Indian Endodontic Society National conference 2011, 200 copies of the questionnaire were circulated amongst the endodontic residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
3
5
1
Order By: Relevance
“…In the present study, only 31% of study participants were willing to do regenerative dental treatment to save teeth and dental tissue, whereas in the study by Utneja et al ,[15] 87.5% of study participants were willing to do the procedure. In the study by Epelman et al [16], 84% of study participants were willing for doing the procedure in the future.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…In the present study, only 31% of study participants were willing to do regenerative dental treatment to save teeth and dental tissue, whereas in the study by Utneja et al ,[15] 87.5% of study participants were willing to do the procedure. In the study by Epelman et al [16], 84% of study participants were willing for doing the procedure in the future.…”
Section: Discussioncontrasting
confidence: 69%
“…In the present study, 57% of study participants agree or partially agree with the statement that it will take more than 20 years to take for some regenerative stem cell therapies to be used in dentistry, whereas in the study by Manguno et al [18] about 92% of study participants agree with the statement. The same result was reposted in the study by Utneja et al [15] and Epelman et al [16] in which 91% and 98% of study participants reported the same, respectively. The recent technique developed in regenerative endodontics is controlling of odontogenic differentiation through involvement of Yes-associated protein.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…A tool developed originally by Epelmen et al and later modified by Utneja et al for a similar study on Indian endodontic residents was used in the current study. [ 5 7 ] We excluded two items, one that we felt was redundant and another asking for the location of the respondents from this tool as the location in our study is restricted to coastal Karnataka. Expert opinion regarding the content validity of this tool was taken by circulating the questionnaire to three endodontic faculties at the level of associate professor/ professor.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%